TEACHER’S STRATEGY IN DEVELOPING ENVIRONMENTAL CARE THROUGH SIMPLE SCIENCE EXPERIMENT TOWARDS ELEMENTARY STUDENTS - Agustin, Mubiar; Nurdiansyah, Deni; Suryana, Sabila Idzni; Sobari, Teti (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2021)
This research was conducted since the decline of sense of responsibility and the concern towards environment. The emergence of various natural disasters is caused by the hands of human itself in taking advantage of natural environment. The objective of this research is to reveal the teacher’s strategy in developing environmental care through simple science experiment. This research uses quantitative approach with survey method regarding to nature of science, simple science experiment, and caring attitude towards the environment. The research data were obtained online by using google form media. There were 224 of elementary school teacher as respondents that become sample of this research, the teachers were from different schools in West Java. The instruments used in this research are questionnaire related to implementation of nature of science and caring attitude towards the environment. The results showed that environmental care attitude to students that had been carried out frequently by the teacher through simple science experiment scored average value 38.5 %. Moreover, the research indicates there were several teachers who had never developing environmental care attitude to their students scored 5.25%. It shows that it is necessary to conduct alternative activity as an improving effort through teacher’s strategy in developing environmental care attitude towards elemntary school student through simple science experiment.